(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Adiantum capillus-veneris, commonly known as maidenhair fern belongs to family Pteridaceae, has traditionally been used in various medicinal preparations as demulcent, expectorant, emmenagogue, diuretic etc. in the form of oil, paste, decoction and powder. It has also prominent role in hair growing and has anti-microbial, anti-inflammatory, anti-diabetic, anti-nociceptive and antioxidant properties of therapeutic interest. This study aimed to investigate the in vitro cytotoxic activity of fractions of ethanolic extract isolated from the aerial part of A. capillus-veneris against some human cancer cell lines such as colon (HCT-116), lung (A549), breast (MCF-7) and pancreatic (MIA PaCa-2) and tumor cell proliferation/inhibition was assessed using MTT assay. The in vivo anticancer activity of hexane fraction was also evaluated against murine Ehrlich ascites carcinoma (EAC) model. The results confirmed that all the fractions of ethanolic extract exhibited promising in vitro inhibition of tumor cell proliferation when tested against different human cancer cell lines. Among all, hexane fraction proved to be more effective having IC50 values 21.72, 22.67, 26.25 μg/mL, for HCT- 116, A-549, MCF-7, respectively, but chloroform fraction revealed to be more cytotoxic against Mia-PACA-2 having IC50 value 14.72 μg/mL. Higher cytotoxic activity is found to be associated with lower IC50 values. The findings showed that all five fractions exhibited dose-dependent killing capabilities in various human derived cancer cell lines at 48 h of treatment. Hexane fraction was found to inhibit tumour growth development by 16.95%, 41.12% and 82.07% at 50, 100 and 200 mg/kg body weight, respectively. Additionally, this fraction was predicted to be non-toxic at the tested doses. The findings indicate that A. capillus-veneris herb is an antineoplastic agent and suggest that further studies evaluating the isolation of active antitumor compounds from A. capillus-veneris and their mechanism(s) of action are necessary.